Knowledge about Negative Effects of Bottle Feeding on Babies’ Dental Tissues Amongst Mothers - Fatima Amer, Darain Zahra Rizvi, Muhammad Shairaz Sadiq, Raid M Aldhafeeri, Zidan M Alanazi, Tahani H Alenzi, Aiman Malik, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Bottle feeding affects the hard tissues of babies in a negative manner. Overall health of infants is also affected by regular bottle feeding. It also results in development of certain harmful habits and increasing use of pacifiers when bottle feeding exceeds 0-6 months. Many detrimental changes occur in the dental tissues of infants due to bottle feeding. Infant feeding practices are an important factor influencing malocclusion in deciduous dentition, which can have long-lasting negative outcomes on oral health-related quality of life. Objective: To assess the awareness in mothers regarding bottle feeding and its adverse dental effects in babies and to find out the general feeding pattern among mothers. Study Design: Descriptive cross sectional study. Study Duration: Study was conducted on feeding mothers in Lahore during a period from November 2020 to February 2021. Methodology: In this study 350 mothers participated. The inclusion criteria consisted of women having at least 1 baby less than 2 years of age. Questionnaire was printed in English and Urdu and filled by mothers. Prior to the actual data collection process at non-sampled Kebeles, the questionnaire was pre-tested on 5% of the sample size, and adjustments were made as necessary. The short questionnaire was collected on same day. Data was analyzed using SPSS version 23 (IBM SPSS Statistics, version 23, USA). Chi square test was used to compare frequencies amongst groups. A p value of <0.05 was set as the level for statistical significance. Results: The results showed that age distribution of mothers included in this study were between 20 to 50 years with 20 to 29 being highest 186 (53.3%). Two hundred and eleven (60.3%) were housewife and one hundred and thirty-nine (39.8%) were working women. Feeding pattern showed that 41% women were breastfeeding their child, 9% were bottle feeding and 50% were using both methods of feeding. Practical implication: In order to identify issues and find solutions to prevent illness and stunted growth, it is important to regularly monitor breastfeeding patterns and feeding practises in mothers. That’s why current study was planned to assess the awareness in mothers regarding bottle feeding and its adverse dental effects in babies and to find out the general feeding pattern among mothers. Conclusion: It is concluded that bottle feeding is more common among women, which is having deleterious effects on both dental and skeletal tissues of babies. Knowledge among mothers related to dental problems as an implication of bottle feeding is generally quite lacking. There needs to be more educational efforts made in order to prevent the dental problems in infants. Keywords: Infant feeding, Breast feeding, bottle feeding, dental, altered occlusion, deciduous dentition, feeding pattern, nutritional demand, tooth decay, discoloration